The joint venture and its partners - Abd Halim, Muhammad Silahuddin; Mohd Amin, Muhammad Amir Azfar; Shahabuddin, Muhammad Syakib Najmii; Mohd Zamashary, Muhammad Hariz; Kamanedin, Kamarulhariz Akmal (2024)
Slide Presentation: “The joint venture and its partners”